Globalization and its Impact on Africa: A Study of Concepts and Effects - Al-Sanusi, Abdul Raouf (Sharwes Scientific Journal, 2025)
This research addresses the phenomenon of globalization and its multidimensional impacts on the African continent. It reviews the historical background of globalization and its development within an economic, cultural, and political context. The research focused on studying the positive and negative impacts of globalization on Africa, particularly in the areas of economy, education, culture, and politics. The study highlighted that globalization has contributed to accelerating the pace of development in some African countries through technology, in addition to enhancing educational opportunities and communication with the outside world. Conversely, the results showed that globalization has deepened the economic gap and increased dependence on major powers. The study concluded with the need to adopt balanced policies that enable African countries to benefit from the advantages of globalization and avoid its negative effects, by promoting regional integration, supporting local industries, and preserving cultural identity